Penerapan Metode Weighted Product pada Sistem Rekomendasi Penyedia Jasa Perbaikan Elektronik untuk Konsumen Startup Servisin - Muhammad Ilyas Zainul Ar Rafii; Julianto Lemantara; Erwin Sutomo (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2023)
Servisin is a new startup with a business process, namely being an intermediary between consumers and electronic equipment service providers/technicians in servicing household electronic equipment. In carrying out its business processes, consumers cannot choose service providers according to the desired criteria, resulting in service providers not in accordance with consumer wishes and will have an impact on consumer satisfaction. Therefore Servisin requires an application-based system that can help recommend service providers to consumers according to the desired criteria. The research method uses the SDLC prototype model with problem solving using the Weighted Product (WP) method in making service provider recommendations. The criteria used are Price, Distance, Rating and Experience. The research resulted in the Servisin application which has a service provider recommendation feature based on the criteria and weights that have been selected, and has been tested using Black Box Testing with an application success percentage of 100%. The survey distributed to 30 respondents said that 93.3% assisted in choosing a service provider according to consumer needs and preferences.